(untitled) (Research, Society and Development, 2022)
The environmental balance can be assessed by observing the characteristics of the environment, and of the population of groups of specific organisms, considered bioindicators. Thus, the objective of this work is to evaluate the edaphic fauna and the litter in two forest fragments in the Southern Amazon, analyzing their use as potential bioindicators. Analyzes were carried out on a forest fragment (A1) and a recovery area (A2), using pitfall traps for edaphic fauna and litter accumulation and decomposition. The analyzes were carried out in two seasons, drought and rain. 357 individuals of the edaphic fauna were collected, the average mass of litter accumulated in the soil was higher in A2 in the dry season in relation to A1 and the decomposition rate for A1 was higher in relation to A2. In the conditions of this study it was possible to observe that the edaphic fauna presented better performance as a bioindicator of environmental quality, when compared to decomposition and accumulation of litter.